2005
DOI: 10.1373/clinchem.2005.049544
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Cleaved β2-Microglobulin in Serum from Patients Undergoing Chronic Hemodialysis

Abstract: Background: Patients on chronic hemodialysis are prone to develop amyloid deposits of misfolded ␤ 2 -microglobulin (␤ 2 M) in osteoarticular tissues. ␤ 2 M with various deletions/truncations and chemical modifications has been found together with structurally intact ␤ 2 M in extracts of ␤ 2 M amyloid fibrils. The state of the circulating population of ␤ 2 M molecules has not been characterized previously with high-resolution methods. Methods: We used immunoaffinity-liquid chromatography-mass spectrometry analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 26 publications
0
27
1
Order By: Relevance
“…Instead, by cleavage of MHC-I-associated b2m at the cell surface [20], soluble db2m molecules can be released to the cellular microenvironment and there perform various functions. In a previous work, we used a newly developed antibody with specificity for db2m [16] and showed that db2m in fact can bind to both human and murine cells even those lacking MHC-I expression [18], suggesting that db2m may bind to the sites other than the MHC-I complexes on the cell surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Instead, by cleavage of MHC-I-associated b2m at the cell surface [20], soluble db2m molecules can be released to the cellular microenvironment and there perform various functions. In a previous work, we used a newly developed antibody with specificity for db2m [16] and showed that db2m in fact can bind to both human and murine cells even those lacking MHC-I expression [18], suggesting that db2m may bind to the sites other than the MHC-I complexes on the cell surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…HYB 332-01 (332-01), a murine monoclonal antibody specific for human db2m variant [16], and anti-human b2m monoclonal antibody 290-03 as purified IgG1 preparations (1 mg ⁄ ml) were obtained from Statens Serum Institut (Copenhagen, Denmark). Human b2m was prepared and purified from the urine of uraemic patients [23] and db2m was produced as described previously [24].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, glycated ␤ 2 -microglobulin has been demonstrated, and shown to induce inflammation in tissue lymphocytes, along with tumor necrosis factor, interleukin-1, and interleukin-6, in the formation of amyloid (9 ). In this issue of Clinical Chemistry, Corlin et al (10 ) confirm that cleaved ␤ 2 -microglobulin occurs and demonstrate that a cleavage product of ␤ 2 -microglobulin, ⌬K58-␤ 2 -microglobulin, behaves differently from normal ␤ 2 -microglobulin during hemodialysis.…”
mentioning
confidence: 98%